The identification of low-pathogenic bacteria on removed spinal implants and implications for antimicrobial prophylaxis - Ann-Kathrin Joerger; Vicki M. Butenschoen; Susanne Feihl; Sebastian Rühling; Jan S. Kirschke; Bernhard Meyer; Sandro M. Krieg (Brain and Spine)
Introduction: The role of low-pathogenic bacteria cultured from removed spinal implants is unclear and the efficacy of perioperative single-dose antibiotics against such bacteria remains underexplored. Research question: This study aims to investigate whether pedicle screw loosening is associated with pathogens and if the choice of perioperative antibiotics can prevent these bacteria. Methods: A retrospective analysis was conducted on 93 patients with implants removed between 01/01/2018 and 03/31/2020. Patients with both loosened and non-loosened implants were included. The latter group was subdivided into cases where implants were exchanged due to adjacent segment degeneration (ASD) and those with elective implant removal after fracture healing. Bacterial cultures from removed implants were analyzed for resistance profiles against the prophylactic single-shot antibiotics administered during implantation. Patients with acute infection, spondylodiscitis, deep wound infection, empyema, and carbon/polyetheretherketone spinal implants were excluded. Results: Bacterial isolates were detected in both loosened (41%) and non-loosened (27%) implants (p = 0.23). The most frequently cultivated bacteria were Cutibacterium acnes and Staphylococcus epidermidis. Sensitivity to the administered antibiotics was 75%. While Cutibacterium acnes was entirely sensitive, Staphylococcus epidermidis was completely resistant. Patients with loosened implants without bacteria had a significantly lower bone mineral density (BMD) than patients with implants removed due to ASD. However, patients with loosened implants and positive bacterial cultures had comparable BMD to ASD patients. Conclusions: The high rate of sensitive Cutibacterium acnes and resistant Staphylococcus epidermidis on removed spinal implants suggests a need to revisit current antimicrobial prophylaxis. Further research is required to determine the clinical significance of low-virulence bacteria, especially on non-loosened implants.